2018
DOI: 10.1007/s11682-018-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Connectometry evaluation in patients undergoing carotid endarterectomy: an exploratory study

Abstract: Introduction: Investigating on brain local connectivity changes following Carotid Endarterectomy (CEA) by connectometry. Methods: In this exploratory study, seventeen subjects (15 males and 2 females, mean age 74.1 years) who underwent CEA, were prospectively recruited. Within one week before the CEA, each patient performed, in the same day, a cognitive evaluation with a Mini Mental State Examination (MMSE) and a Magnetic Resonance (MR) exam that included a DTI sequence for the connectometry analysis. The same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
2
5
0
Order By: Relevance
“…Although the partial knowledge of the mechanisms underlying neurocognition limits the interpretation of our results, it is reasonable to conclude that the cognitive improvements observed after CEA, in analogy to what seen for CAS [41], are partly determined by a reassessment of regional neural activity of several brain areas. These findings tend to confirm the trend observed in literature, in particular the hypothesis that the improved cerebral perfusion following revascularization procedures induces a series of rearrangements of brain activity and networking that could explain the observed improvements in cognitive performances [18,40,42].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the partial knowledge of the mechanisms underlying neurocognition limits the interpretation of our results, it is reasonable to conclude that the cognitive improvements observed after CEA, in analogy to what seen for CAS [41], are partly determined by a reassessment of regional neural activity of several brain areas. These findings tend to confirm the trend observed in literature, in particular the hypothesis that the improved cerebral perfusion following revascularization procedures induces a series of rearrangements of brain activity and networking that could explain the observed improvements in cognitive performances [18,40,42].…”
Section: Discussionsupporting
confidence: 90%
“…The authors further observed using DTI an improvement of the mean values of fractional anisotropy of the white matter located in the hemisphere ipsilateral to surgery and in the contralateral anterior cerebral artery territory. A subsequent connectometry study by Porcu M et al [42] showed that the short-term • 88 voxels (1%) covering 6% of atlas.SPL l (superior parietal lobule left) • 76 voxels (1%) covering 6% of atlas.PaCiG r (paracingulate gyrus right) • 59 voxels (1%) covering 2% of atlas.SFG r (superior frontal gyrus right) • 28 voxels (0%) covering 1% of atlas.sLOC r (lateral occipital cortex, superior division right) • 26 voxels (0%) covering 0% of atlas.FP r (frontal pole right) • 26 voxels (0%) covering 3% of atlas.aSMG r (supramarginal gyrus, anterior division right) • 21 voxels (0%) covering 3% of atlas.IFG oper r (inferior frontal gyrus, pars opercularis right) • 16 voxels (0%) covering 3% of atlas.IFG tri r (inferior frontal gyrus, pars triangularis right) • 8 voxels (0%) covering 3% of atlas.FO r (frontal operculum cortex right) • 4 voxels (0%) covering 0% of atlas.Precuneous (precuneous cortex) • 3 voxels (0%) covering 0% of atlas.AG r (angular gyrus right) • 1 voxels (0%) covering 0% of atlas.pSMG r (supramarginal gyrus, posterior division right) • 2951 voxels (47%) covering 1% of atlas.not-labeled changes in interhemispheric local connectivity in the corpus callosum and cerebellum following CEA tend to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…It may be that CEA prevents reductions in FA in the hippocampal portion of the cingulum bundle. This result is consistent with the ndings of Porcu et al (Porcu et al, 2019), who found increases in cognitive performance and white matter connectivity following CEA.…”
Section: Discussionsupporting
confidence: 93%
“…Future research should focus on neuroanatomical changes after carotid revascularization, and this is indeed one of the main goals of randomized clinical trials in this community (Howard et al, 2017 ; Marshall, Asllani, Pavol, Cheung, & Lazar, 2017 ). Increasing evidence suggests that revascularization can simultaneously improve cerebral hemodynamics, reverse cognitive deterioration (Lattanzi et al, 2019 ; Lattanzi et al, 2020 ), and even renormalize functional connectivity in the advanced networks (Porcu et al, 2019 ; Porcu et al, 2020 ). Third, we did not take into account the role of clinically silent lacunar infarcts in cognitive impairment in the sample of patients analyzed.…”
Section: Discussionmentioning
confidence: 99%